PENJADWALAN DAN ALOKASI MATERIAL PADA PROYEK PENINGKATAN RUAS JALAN KANTO-PULAHENTI DENGAN MENGGUNAKAN METODE LOB (LINE OF BALANCE) - Yasin, Vannyarti; Fuad, Mohamad Januar; Rachman, Ari Putra (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
The purpose of this research is to plan the timing of material usage and determine the material requirements at the Kanto – Pulahenti road improvement project site. This research method discusses scheduling techniques and material allocation in a construction project using the Line Of Balance (LOB) method. Data collection was conducted through field surveys to obtain primary data, which includes direct observations that can influence planning and allocation of heavy equipment, such as distance, time, and working conditions on site. From the analysis of the construction project data for the Kanto – Pulahenti road, using the Line of Balance (LOB) method allows for detailed planning of material usage, highlighting the execution time and the duration required for the construction project. The duration needed for the construction work on the Kanto - Pulahenti road using the Line of Balance (LOB) method is 26 weeks. However, scheduling with the Line of Balance (LOB) method would be more effective if the data obtained for the project were more detailed. This research is expected to provide guidance for students and others in the theoretical and practical realms of civil engineering, particularly in the context of scheduling and material allocation in projects.